2003
DOI: 10.1182/blood-2003-01-0031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the recurrent unbalanced translocation der(1;7)(q10;p10)

Abstract: An unbalanced translocation der(1;7)(q10; p10) is a nonrandom chromosomal aberration commonly observed in myelodysplastic syndrome and acute myeloid leukemia. We molecularly analyzed the breakpoints of der(1;7)(q10;p10) by quantitative fluorescent in situ hybridization (FISH) analyses using centromeric satellite DNAs mapped to chromosomes 1 and 7 as probes. We found that the signal intensities of 2 centromere alphoid probes, D1Z7 on chromosome 1 and D7Z1 on chromosome 7, were almost invariably reduced on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
6
17
0
Order By: Relevance
“…The t(3;5)(q25;q34) translocation, seen in one of our patients, rearranges NPM gene with MLF1 gene and related to MDS progression to AML. 22 Translocations involving chromosome 1 were also observed in two cases of der(1;7)(q10;p10), as previously reported in MDS, 23 and in one case with t(1;2)(q21;q37) in our series, in which we identified a new HHL (human hornerin like) gene on 1q21 and showed that its overexpression might be related to MDS/AML transformation (manuscript prepared by YY Wang, SJ Chen et al).…”
Section: Discussionsupporting
confidence: 61%
“…The t(3;5)(q25;q34) translocation, seen in one of our patients, rearranges NPM gene with MLF1 gene and related to MDS progression to AML. 22 Translocations involving chromosome 1 were also observed in two cases of der(1;7)(q10;p10), as previously reported in MDS, 23 and in one case with t(1;2)(q21;q37) in our series, in which we identified a new HHL (human hornerin like) gene on 1q21 and showed that its overexpression might be related to MDS/AML transformation (manuscript prepared by YY Wang, SJ Chen et al).…”
Section: Discussionsupporting
confidence: 61%
“…Together with the 2 1p and 3 1q subtelomere signals (data not shown), this FISH pattern defines a der(1,7)(q10;p10), a nonrandom chromosome rearrangement that is highly specific for a particular subset of neoplastic myeloid disorders. 41,42 Although these findings corroborate a potential biologic link between the phenomenon described herein and the recently documented acquired partial uniparental disomies in AML, the small homozygous stretch surrounding the RHD/ RHCE gene region in this instance also implied that its underlying somatic recombination event was not directly linked with the one generating the chromosomal abnormality. 41,43,44 Rh antigen and Rh complex molecule expression levels of D-negative red cell subpopulations reflect the mechanisms of loss of heterozygosity…”
Section: Spontaneous Rh Phenotype Splitting Caused By Either Somatic supporting
confidence: 83%
“…The leukemia was characteristic of t-AML in showing trilineage myelodysplastic features. Furthermore, the unbalanced translocation der(1;7)(q10;p10), resulting effectively in monosomy 7q (7qÀ), was also typically found in t-AML/MDS [7]. Therefore, according to the current World Health Organization classification scheme, the leukemia was classified as t-AML.…”
Section: Discussionmentioning
confidence: 99%